Influence of microwave polymerization method and thickness on porosity of acrylic resin - Pero, Ana Carolina [UNESP] [UNESP]; Barbosa, Débora Barros [UNESP]; Marra, Juliê [UNESP]; Ruvolo-Filho, Adhemar Colla [UNESP]; Compagnoni, Marco Antonio [UNESP] (Wiley, 2008)
Purpose: This study evaluated the influence of polymerization cycle and thickness of maxillary complete denture bases on the porosity of acrylic resin. Materials and Methods: Two heat-activated denture base resins - one conventional (Clássico) and one designed for microwave polymerization (Onda-Cryl) - were used. Four groups were established, according to polymerization cycles: A (Onda-Cryl, short microwave cycle), B (Onda-Cryl, long microwave cycle), C (Onda-Cryl, manufacturing microwave cycle), and T (Clássico, water bath). Porosity was evaluated for different thicknesses (2.0, 3.5, and 5.0 mm; thicknesses I, II, and III, respectively) by measurement of the specimen volume before and after its immersion in water. The percent porosity data were submitted to Kruskal-Wallis for comparison among the groups. Results: The Kruskal-Wallis test detected that the combinations of the different cycles and thicknesses showed significant differences, and the mean ranks of percent porosity showed differences only in the thinnest (2.0 mm) microwave-polymerized specimens (A = 53.55, B = 40.80, and C = 90.70). Thickness did not affect the results for cycle T (I = 96.15, II = 70.20, and III = 82.70), because porosity values were similar in the three thicknesses. Conclusions: Microwave polymerization cycles and the specimen thickness of acrylic resin influenced porosity. Porosity differences were not observed in the polymerized resin bases in the water bath cycle for any thickness. © 2007 by The American College of Prosthodontists.
Keywords: Acrylic resin; Complete denture; Polymerization method; Porosity; acrylic acid resin; biomedical and dental materials; poly(methyl methacrylate); polymer; water; absorption; chemistry; comparative study; denture; heat; human; materials testing; microwave radiation; porosity; pressure; radiation exposure; surface property; temperature; time; Absorption; Acrylic Resins; Dental Materials; Denture Bases; Denture, Complete, Upper; Heat; Humans; Materials Testing; Microwaves; Polymers; Polymethyl Methacrylate; Pressure; Surface Properties; Temperature; Time Factors; Water